2023
DOI: 10.3389/fmolb.2023.1246728
|View full text |Cite
|
Sign up to set email alerts
|

Hippophae rhamnoides L. (sea buckthorn) mediated green synthesis of copper nanoparticles and their application in anticancer activity

Pooja Dadhwal,
Harish Kumar Dhingra,
Vinay Dwivedi
et al.

Abstract: Green synthesis of nanoparticles has drawn huge attention in the last decade due to their eco-friendly, biocompatible nature. Phyto-assisted synthesis of metallic nanoparticles is widespread in the field of nanomedicine, especially for antimicrobial and anticancer activity. Here in the present research work, investigators have used the stem extract of the Himalayan plant Hippophae rhamnoides L, for the synthesis of copper nanoparticles (CuNPs). The synthesized of CuNPs were analyzed by using sophisticated inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 99 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Microbes have various enzymes, metabolites, and pigments that are responsible for transforming metal ions into metal oxides or metallic NPs (Choudhary et al, 2023 ). To date, metallic NPs have been synthesized by bacteria, fungi, actinomycetes, algae, and viruses (Choudhary et al, 2023 ; Dadhwal et al, 2023 ). Several investigators have synthesized TiO 2 NPs by using all these types of microorganisms.…”
Section: Synthesis Of Tio 2 Npsmentioning
confidence: 99%
“…Microbes have various enzymes, metabolites, and pigments that are responsible for transforming metal ions into metal oxides or metallic NPs (Choudhary et al, 2023 ). To date, metallic NPs have been synthesized by bacteria, fungi, actinomycetes, algae, and viruses (Choudhary et al, 2023 ; Dadhwal et al, 2023 ). Several investigators have synthesized TiO 2 NPs by using all these types of microorganisms.…”
Section: Synthesis Of Tio 2 Npsmentioning
confidence: 99%
“…In recent years, research has shown that sea buckthorn can help with illness prevention and healing, including viral infections and cancer (15,28) owing to its antioxidant (29,30), anti-inflammatory (31), antiviral (32), antimicrobial (24, 30, 33), and antibacterial (34, 3 5 ) p r o p e r t i e s . C a r d i o p r o t e c t i v e , a n t i -a t h e r o g e n i c , hepatoprotective, hypolipidemic (29,36,37), dermatological (4), antiproliferative (20), and anticancer (e.g., colon, liver, lung, cervical, ovarian, and breast cancer cells) effects have been reported, too (6,15,38).…”
Section: Physiological and Therapeutic Actionsmentioning
confidence: 99%
“…Nanomaterials (NMs) possess unique properties that are not found in the bulk state and have been utilized in a wide range of industries, including electronics ( Wu, 2017 ), energy ( Wang et al, 2020 ), medicine ( Sim and Wong, 2021 ; Dadhwal et al, 2023 ), food ( McClements and Xiao, 2017 ), and cosmetics ( Fytianos et al, 2020 ). With the increasing use of NMs, their toxicity concerns are growing.…”
Section: Introductionmentioning
confidence: 99%